ANÁLISE DAS MONOGRAFIAS EXIGIDAS COMO TRABALHO DE CONCLUSÃO DE CURSO DE FISIOTERAPIA DA UEG, UNU GOIÂNIA, ESEFFEGO EM RELAÇÃO À ADEQUAÇÃO À RESOLUÇÃO 196 DO CNS DESDE 1996 ATÉ 2006 (Movimenta (ISSN 1984-4298), 2018)
The creation and the functioning of the Committees of Ethics in Research (CER) in Brazil is regulated by the Resolution 196 since it was published by the National Council of Health (CNS). The research protocol of any research involving human beings is obligatorily submitted to a CER to obtain its letter of approval. The objective of this article was to analyze the adequacy from the demanded monographs as work of course conclusion from Physiotherapy of the State University of Goiás (UEG), University Unit of Goiânia, Superior School of Physical Education and Physiotherapy of the State of Goiás (ESEFFEGO) in relation to the Resolution 196/96. It was analyzed if the research protocol of the same ones had been, when necessary, submitted to the CER. The method used was a bibliographical research carried out in all monographs produced by the Physiotherapy course of ESEFFEGO since 1996 up to 2006 available in the library of ESEFFEGO. The observed result was that from the 286 found monographs, 193 (100%) of these must have had its research protocols submitted to the approval of a CER. Only 35 (18%) of this total had its research project submitted to the approval of a CER, while 158 (82%) of this total had not been submitted to the approval of a CER. It is stated out the imperious necessity of creation of a CER in ESEFFEGO.